The Symbolic Meaning of the Melinting Dance in Wana Village, East Lampung - Dwi Tiya Juwita; Susi Wendhaningsih (Universitas Negeri Padang, 2024)
This research aims to find the symbolic meaning of the Melinting dance in Wana village, East Lampung. This research uses an interdisciplinary approach consisting of the disciplines of Anthropology of Art and Sociology of Art. The type of research used is qualitative with descriptive analysis methods. Data collection techniques consist of observation, interviews and document study. The data validity technique used is the source triangulation technique. The data analysis technique is carried out in three stages, namely by reducing data, presenting data, and drawing conclusions. The research results show that the symbolic meaning of the Melinting dance can be seen from the main elements (movement) and supporting elements (musical accompaniment and clothing). The symbolic meaning of the Melinting dance in movement is being open, respecting each other, being good at maintaining attitudes and behavior, maintaining the dignity of the family, being responsible and having the courage to look after oneself. The symbolic meaning of the Melinting dance accompanied by music is an expression of joy, community skill and peaceful life. Meanwhile, the symbolic meaning of fashion is that people's behavior must be in accordance with the teachings of the Islamic religion.